Global analysis of foreign direct investment outflows and its determinants. - Lee, Gladwin Khian Guan. (2008)
The aim of this paper is to evaluate the determinants of FDI Outflows. We consider macroeconomic factors, such as gross domestic production, exchange rate, inflation, interest rate, domestic investment, openness of the economy and another measure, Corruption Perception Index as possible factors. The model developed identifies the main determinants of outward FDI using time series data for thirty nine countries.